2012
DOI: 10.7904/2068-4738-iii(06)-86
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Biology of Freshwater Prawn Macrobrachium Vollenhovenii (Herklot, 1857) Caught in Warri River

Abstract: A total number of 338 specimens of Macrobrachium vollenhovenii were bought from fisher folks who fished from Ubeji, Jala and Soroghagbene; but marketed their landings at Ubeji. Specimens were collected at monthly intervals between March and November, 2011. The male to female sex ratio established was 1:2:3. The size at first maturity was 9.0 cm for males and 10.0 cm for females. The length-weight relationship revealed an increase in total length of each specimen as body weight increased. The regression coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
(2 reference statements)
3
4
1
Order By: Relevance
“…The follicle increased in size and volume. Similar observation was made in the same species by 42 . In M. vollenhovenii, the diameter of the cells increases from 2 μm to 40 μm on average during previtellogenesis and reaches 200 to 250 μm during vitellogenesis.…”
Section: Discussionsupporting
confidence: 89%
“…The follicle increased in size and volume. Similar observation was made in the same species by 42 . In M. vollenhovenii, the diameter of the cells increases from 2 μm to 40 μm on average during previtellogenesis and reaches 200 to 250 μm during vitellogenesis.…”
Section: Discussionsupporting
confidence: 89%
“…This implied that fecundity was not a measure of size and the relationship was insignificant. Little wonder why small-sized prawn was observed from this research to possess eggs, a similar situation also observed by [37] on M. lamarrei and [15] on M. vollenhovenii [34], reported that there was no correlation between fecundity and total weight of M. vollenhovenii [38], reported a decline in the number of eggs with an increase in the size of Penaeus plebejus and found out that this could possibly be due to ovarian senescence in large (old) females.…”
Section: Discussionsupporting
confidence: 83%
“…These results were found to be less in comparison to that of M. macrobrachion in this study. The findings from this work showed that this species had low fecundity when compared with M. vollenhovenii from other works as reported by [15,33,34]. This might be due to the fact that M. vollenhovenii is larger than M. macrobrachion.…”
Section: Discussionsupporting
confidence: 45%
“…In addition, maturity is also related to size in this genus. Females become mature at a larger size than males in M. völlenhoveni and in Macrobrachium amazonicum (Olele & Okonkwo ; Pantaleão et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the opposite can be observed (Bauer & Delahoussaye ). Moreover, size at maturity also differs between sexes in Macrobrachium (Mantel & Dudgeon ; Olele & Okonkwo ; Pantaleão et al. ).…”
mentioning
confidence: 99%